When Products and Brands Trade Hands: A Framework for Acquisition Success. Issue 2 (2nd April 2016) - Newmeyer, Casey E.; Swaminathan, Vanitha; Hulland, John
Abstract : This research examines the influence of a firm's focus on either products or brands in an acquisition announcement on investor reactions and value creation for the acquiring firm. We conduct an event study of product and brand acquisitions in multiple business-to-consumer industries over a 30-year period (1980–2012). We find that value creation from such acquisitions depends on target resource strength and resource fit (relatedness between the acquirer's and target's product offerings). Further, the acquirer's marketing management capability and product line diversification affect the ability of the firm to engage in resource transfer following the acquisition.